Model-driven framework to support evolution of mobile applications in multi-cloud environments. Issue 3 (5th September 2016) - Chondamrongkul, Nacha
Abstract : Purpose: The development of mobile applications in multiple clouds environment is a complex task because of the lack of platform standards in cloud computing and mobile computing. The source code involves various proprietary programming libraries for different platforms. However, functionalities are inevitably changed over time, as well as the platform. Therefore, a great deal of development effort is required, when changes need to be made at functional and platform level. This paper aims to propose SIMON, a framework that eases complexity of the development to support software evolution. Design/methodology/approach: SIMON shields the developer from the complexity of mobile and cloud platforms in the development of mobile applications in multiple clouds environment. The framework uses model of application design to automate the development and support execution of mobile applications in system environment that needs integration to the number of data sources located on multiple clouds. The framework is composed of prefabricated components that support function changeability and platform adaptability. Findings: The framework is examined with the development of a sample application. After it is evaluated with scenarios that involve changing at functional and platform levels, the result shows significant reducing of the development effort by comparing with the other approaches. Originality/value: The framework facilitates the implementation of mobile applications in the software system that involves integration to multiple clouds, and it supports software evolution with lesser development effort.